THE INFLUENCE OF BRAND IMAGE, INTERNET MARKETING ON STUDENTS' DECISIONS TO CHOOSE MALAHAYATI UNIVERSITY. - Pratama, Reza Hardian; Manan, Mohammad Athian; Pratama, Muhammad Irfan; Sejati, Hiro; Khotimah, Ayyumi Khusnul (Jurnal Manajemen, 2024)
Students' decisions in choosing a university are influenced by the brand image and internet marketing carried out by the agency/company. The use of data collection in this research is the purposive sampling method, with the Heirs formula, namely 20 indicators x 10, namely 200 sampling, the analytical tool used in the research is Smart Pls 3.0, the findings obtained in this research are positive Brand Image and are significant for student decisions Choosing Malahayati University, social media is positive and significant for the decision to choose students at Malahayati University, Website is positive and significant for the decision to choose Malahayati University, advice obtained from research results, website maintenance which is sometimes late compared to social media for the latest information in providing information on the website . The results that have been obtained by websites that do not provide the latest information for information seekers do not provide information that is comprehensive and easy to understand. This must be taken into greater consideration by information seekers in searching for information for universities. The results that have been obtained are that the latest information meets the needs they have Information seekers want via social media to not be able to provide information quickly and accurately.